Waves of Sound: : the Reinado de Nossa Senhora do Rosário - Dias de Amorim, Anna Cariny; Amorim Moura, Heleniara (Revista Brasileira de Estudos da Presença, 2025)
This article echoes the importance of attentive listening to both noise and subtlety in order to grasp the richness of the Reinado de Nossa Senhora do Rosário (Our Lady of the Rosary) in Divinópolis, Minas Gerais (Brazil). The proposed discussion considers the soundscape of the Reinado in conjunction with the Bantu philosophy of Vital Force. The listening that guided the path of this writing stems from the author’s experience as a member of the Terno de Moçambique from the Interlagos neighborhood. The sounds that inhabit the festival are presented as poetic elements that echo and shape the history of the Reinado and provide a form of community resistance that sustains the culture and memory of Afro-descendant peoples in the Central-West region of Minas Gerais.